2015
DOI: 10.1001/jamafacial.2015.0978
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of Improvement in Nasal Obstruction Following Nasal Valve Correction in Patients With a History of Failed Septoplasty

Abstract: IMPORTANCE Patients with a septal deviation and concerns about nasal obstruction often undergo septoplasty to improve nasal airflow. Following primary septoplasty, however, some patients have persistent symptoms due to nasal valve dysfunction and may require nasal valve surgery. OBJECTIVES To evaluate the change in disease-specific quality of life for patients who undergo nasal valve correction after failed septoplasty using the Nasal Obstruction Symptom Evaluation (NOSE) survey and to determine whether identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 16 publications
(23 reference statements)
3
57
0
1
Order By: Relevance
“…The static component in nasal valve dysfunction is commonly treated with spreader grafts and extracorporeal septal reconstruction . Dynamic nasal valve collapse (NVC), although as common as septal deviation and inferior turbinate hypertrophy, is often underdiagnosed and left untreated . Batten grafts, bone‐anchored sutures, and lateral crural strut grafts are common methods in functional rhinoplasty to address dynamic NVC.…”
Section: Introductionmentioning
confidence: 99%
“…The static component in nasal valve dysfunction is commonly treated with spreader grafts and extracorporeal septal reconstruction . Dynamic nasal valve collapse (NVC), although as common as septal deviation and inferior turbinate hypertrophy, is often underdiagnosed and left untreated . Batten grafts, bone‐anchored sutures, and lateral crural strut grafts are common methods in functional rhinoplasty to address dynamic NVC.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ideal follow‐up duration after functional septorhinoplasty has not yet been determined. Previous literature utilizing NOSE scores report variable follow‐up, ranging from 1 month to 4 years …”
Section: Introductionmentioning
confidence: 99%
“…Nasal valve correction using spreader grafts in another nasal obstruction population showed similar outcomes, who had preoperative NOSE scores of over 80 and postoperative scores reaching 22.2. 26 A study using a homemade questionnaire also showed significant improvement in nasal symptom scores after autospreader grafting. 18 These…”
Section: Discussionmentioning
confidence: 95%